Sistem Pengendalian Persediaan Bahan Baku dengan Metode Economic Order Quantity pada PT Kayu Lapis Indonesia di Kaliwungu - Auliya Ma’rifatul Jannah; Sukemi Kamto Sudibyo (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
The central aims of diagnosing pressing difficulties and gauging the advantageous repercussions of a sistem for raw material inventory control were addressed in a study published in 2026, identified as